Volume reconstruction by using 4D object surface data - Wehr, Aloysius; Ioannides, Marinos (My University, 1994)
Today noncontacting optical 3D digitizers feature high sampling rates and are capable of obtaining highly resolved 3D images of object surfaces. In general these digital-range images contain a large amount of data and require powerful computers and large memories for further processing. It is shown that the number of data can be reduced by eliminating the redundant information contained in digital range images by applying pattern recognition techniques. Surface generation, contour lines generation, triangulation, and volume generation are explained for the different operation levels with respect to CAD/CAM.
Keywords: 3D images